Social media in the marketing of educational services - Tokarski, Daniel; Kowalik, Maximilian (Journal of Positive Management, 2022)
Purpose: The aim of the article is to present the results of the analysis of the University’s educational services promotion strategy with the participation of social media in the process of acquiring and maintaining lasting relationships with stakeholders. Methodology: The research concerned the quality of service to stakeholders of the Pope John Paul II State School of Higher Education in Biala Podlaska, (Poland, Lubelskie Voivodeship) and the level of their satisfaction with promotional activities undertaken by the analyzed entity, as well as the determinants of choosing the place of education in correlation with the possibilities of sustainable development. Empirical research was conducted in the third quarter of 2020 using an on-line questionnaire, based on the deliberate selection of respondents. Findings: The analysis of the results focused on promotional activities that the examined entity should keep or develop on the pages of selected social networks. Acquiring new fans was indicated as the best-rated activities of the University, which directly translates into the visibility and range of the generated content. According to the respondents, the surveyed entity should publish content more often via social media in order to build lasting relationships with the immediate environment. Implications: According to the respondents, the University should publish more content on the Internet. Respondents indicated that other students may be helpful in publishing posts. The survey showed that most of the respondents recommended the University to their friends thanks to the earlier reading of its offer on the Internet, on one of the social networks. Originality: An original scientific article on the use of social media in the promotion of educational services, the first references to it appear in the literature on the subject at the beginning of the 21st century. Keywords: internet, educational services, marketing services, social media Paper type: Research paper